2018
DOI: 10.3389/fmicb.2018.01528
|View full text |Cite
|
Sign up to set email alerts
|

Differential Functions of Two Metalloproteases, Mrmep1 and Mrmep2, in Growth, Sporulation, Cell Wall Integrity, and Virulence in the Filamentous Fungus Metarhizium robertsii

Abstract: The Metarhizium genus of filamentous entomopathogenic fungi plays a pivotal role in regulating insect populations. Metalloproteases (MEPs) are a widely distributed and diverse family of hydrolytic enzymes that are important toxicity factors in the interactions between fungi and their hosts. Herein, we characterized two MEPs, Mrmep1 and Mrmep2, in Metarhizium robertsii using gene deletion. Growth rates of the resulting ΔMrmep1 and ΔMrmep2 mutants decreased by 16.2 and 16.5%, respectively, relative to the wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
(41 reference statements)
1
16
0
1
Order By: Relevance
“…The transcriptional profiles of RcMEP2, RcMEP3, RcMEP4, and RcMEP5 were examined during the infection process to wheat basal sheaths/stems, including five different inoculation time points (18,36,72,96, and 240 h post inoculation (hpi)) and in vitro culturing hypha. Quantitative RT-PCR (qRT-PCR) analyses indicated that during in vitro culturing, RcMEP2, RcMEP3, RcMEP4, and RcMEP5 displayed a very low transcriptional level set as 1, respectively.…”
Section: Transcriptional Profiles Of Rcmep2-rcmep5 During the Fungus mentioning
confidence: 99%
See 2 more Smart Citations
“…The transcriptional profiles of RcMEP2, RcMEP3, RcMEP4, and RcMEP5 were examined during the infection process to wheat basal sheaths/stems, including five different inoculation time points (18,36,72,96, and 240 h post inoculation (hpi)) and in vitro culturing hypha. Quantitative RT-PCR (qRT-PCR) analyses indicated that during in vitro culturing, RcMEP2, RcMEP3, RcMEP4, and RcMEP5 displayed a very low transcriptional level set as 1, respectively.…”
Section: Transcriptional Profiles Of Rcmep2-rcmep5 During the Fungus mentioning
confidence: 99%
“…After purification, these His-TF-RcMEP2, His-TF-RcMEP2-1, and His-TF-RcMEP2-2 proteins were checked using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) ( Figure 3C). stems/sheaths, including five different infection time points (18,36,72,96, and 240 h post inoculation (hpi)) and compared to in vitro culturing. Error bars were calculated based on three replicates.…”
Section: Rcmep2 and Its M35 Domain-containing Peptides Induce Cell Dementioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effects of MrGpa1 on virulence, bioassays with Galleria mellonella larvae (RuiQing Bait, Shanghai, China) were performed as described previously (Zhou et al 2018). The larvae were immersed in conidial suspension (1 ´ 10 6 conidia /ml) for 90 s or injected (into the hemocoel) with 10 ml of conidial suspensions (1 ´ 10 5 conidia /ml) and incubated at 25 °C, Each treatment was performed in triplicate, with 18 larvae in each group.…”
Section: Phenotype Assaysmentioning
confidence: 99%
“…Abuse of pesticides have caused serious threats to human health, environment, and the extinction of beneficial species (Gao et al, ; J. Xiao et al, ; J. J. Xiao et al, ). In recent years, more studies have focused on the development of biological approaches to effectively control S. litura (Li et al, ; Liu, Chen, Li, Yang, & Long, ; Wang et al, ; Zhou, Zhou, Fan, Wang, & Huang, ). The immune system of insects plays a crucial role in the success of biological control measures (Luo et al, ; Qian et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%